2014
DOI: 10.1039/c4mb00155a
|View full text |Cite
|
Sign up to set email alerts
|

An inverse small molecule screen to design a chemically defined medium supporting long-term growth of Drosophila cell lines

Abstract: Drosophila cell culture is used as a model system with multiple applications including the identification of new therapeutic targets in screens, the study of conserved signal transduction pathway mechanisms, and as an expression system for recombinant proteins. However, in vitro methods for Drosophila cell and organ culture are relatively undeveloped. To characterize the minimal requirements for long-term maintenance of Drosophila cell lines, we developed an inverse screening strategy to identify small molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 79 publications
(163 reference statements)
0
16
0
Order By: Relevance
“…3). ZB media was engineered to support long-term proliferation and passaging of the wing-disc derived Cl.8 cell line (23). These results demonstrate that specific chemical stimulation by FEX is specifically required for the generation of both spontaneous and mechanically stimulated ICWs.…”
Section: Icws Require a Chemical Signalmentioning
confidence: 86%
“…3). ZB media was engineered to support long-term proliferation and passaging of the wing-disc derived Cl.8 cell line (23). These results demonstrate that specific chemical stimulation by FEX is specifically required for the generation of both spontaneous and mechanically stimulated ICWs.…”
Section: Icws Require a Chemical Signalmentioning
confidence: 86%
“…Surprisingly, we observed Ca 2+ oscillations in Clone 8 without fly extract ( Fig. 2G, Movie S11) in a chemically defined media (Burnette et al, 2014). These oscillations occurred on the scale of roughly one per minute ( Fig.…”
Section: Oscillatory Ca 2+ Signal Exhibits Four Categories Of Ca 2+ Amentioning
confidence: 84%
“…2). We used ex vivo culture in the chemically-defined ZB media to reduce the effect of batch variability (Burnette et al, 2014). Although the accompanying paper shows that ZB media with 2.5% fly extract best recapitulates in vivo Ca 2+ dynamics (DEVELOP 2017/159251), we found that 15% fly extract was ideal to yield oscillatory signals of sufficient strength for reliable quantification.…”
Section: Results and Discussion A Novel Pipeline For Spatial Analysismentioning
confidence: 99%
“…1d, d', Extended Data Movie 1). However, in vivo imaging provides limited information due to larval motion, mechanical compression, and an inability to specifically perturb the organ with drugs [25][26][27] .…”
Section: Fly Serum Based Extracts Stimulate Icws Ex Vivomentioning
confidence: 99%
See 1 more Smart Citation